2004
DOI: 10.1103/physrevb.70.214501
|View full text |Cite
|
Sign up to set email alerts
|

Critical current in Nb-Cu-Nb junctions with nonideal interfaces

Abstract: We report on experimental studies of superconductor (Nb) -normal metal (Cu) -superconductor (Nb) junctions with dirty interfaces between the different materials. By using a set of simultaneously prepared samples, we investigated the thickness dependence as well as the temperature dependence of the critical currents in the junctions. Good agreement between the decay of the measured critical currents and theoretical calculations was obtained without any fitting parameters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
(8 reference statements)
1
14
0
Order By: Relevance
“…20 For the ideal junction, I C / R À1 N in which R N ¼ ql=A is the normal-state resistance of the SNS junction, q ¼ 1=ð F e 2 DÞ is the island resistivity, A is the island cross section, F is the density of states at the Fermi level in N, and D is the diffusion coefficient of the normal metal. [21][22][23] The hysteresis is suppressed at low temperatures by increasing the Josephson inductance of the junction. 23,24 We achieved this by shrinking the cross section A of the weak-link which leads to an increased normal-state resistance and Josephson inductance.…”
mentioning
confidence: 99%
“…20 For the ideal junction, I C / R À1 N in which R N ¼ ql=A is the normal-state resistance of the SNS junction, q ¼ 1=ð F e 2 DÞ is the island resistivity, A is the island cross section, F is the density of states at the Fermi level in N, and D is the diffusion coefficient of the normal metal. [21][22][23] The hysteresis is suppressed at low temperatures by increasing the Josephson inductance of the junction. 23,24 We achieved this by shrinking the cross section A of the weak-link which leads to an increased normal-state resistance and Josephson inductance.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The analysis of existing experimental data 16,17 have shown that the value of exchange energy H in ferromagnetic materials used in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] scales is in between 850 and 2300 K. This leads to effective decay length F1 Ϸ 1.2-4.6 nm and period of oscillations F2 Ϸ 0.3-2 nm of thickness dependence of a S/F/S junction critical current I C . These values turned out to be much smaller compared to the decay length N Ϸ 10-100 nm, in similar S/normal metal ͑N͒/S structures.…”
Section: Introductionmentioning
confidence: 97%
“…SFS junctions have been realized experimentally by several groups. [19][20][21][22][23][24][25][26][27][28][29] In d-wave superconductor junctions, one of the most remarkable phenomena is the formation of midgap Andreev resonant states ͑MARSs͒ at interfaces. 30 The MARSs stem from a sign change of pair potentials of d-wave superconductors.…”
Section: Introductionmentioning
confidence: 99%